The atypical RhoU/Wrch1 Rho GTPase controls cell proliferation and apoptosis in the gut epithelium. (12th March 2019) - Slaymi, Chaker; Vignal, Emmanuel; Crès, Gaëlle; Roux, Pierre; Blangy, Anne; Raynaud, Peggy; Fort, Philippe
Abstract : Background: The mammalian gut epithelium displays among the highest rates of self‐renewal, with a turnover time of less than 5 days. Renewal involves concerted proliferation at the bottom of the crypt, migration and differentiation along the crypt‐villus axis and anoïkis/shedding in the luminal epithelium. Renewal is controlled by interplay between signalling pathways, among which canonical and non‐canonical Wnt signals play prominent roles. Overall 92% of colon tumours show increased canonical Wnt signalling resulting from mutations, established as major driver steps towards carcinogenesis. Results: Here, we examined the physiological role of RhoU/Wrch1 in gut homeostasis. RhoU is an atypical Rho GTPase related to Cdc42/Rac1 and identified as a transcriptional target of non‐canonical Wnt signalling. We found that RHOU expression is reduced in human colorectal tumour samples. We show that RhoU is mainly expressed in the differentiated compartment of the gut epithelium. Rhou specific invalidation in the mouse gut elicits cell hyperplasia and is associated in the colon with a highly disorganized luminal epithelium. Hyperplasia affects all cell types in the small intestine and colon and has a higher impact on goblet cells. Hyperplasia is associated with a reduction of apoptosis and an increased proliferation. RhoU knockdown in human DLD‐1 colon cancer cells also elicits a higher growth index and reduces cell apoptosis. Last, loss of RhoU function in the mouse gut epithelium or in DLD‐1 cells increases RhoA activity and the level of phosphorylated Myosin Light Chain‐2, which may functionally link RhoU activity to apoptosis. Conclusion: RhoU is mostly expressed in the differentiated compartment of the gut. It plays a role in homeostasis as its specific invalidation elicits hyperplasia of all cell types. This mainly results from a reduction of apoptosis, through actomyosin‐dependent mechanisms. Significance: RhoU negatively controls cell growth in the intestinal epithelium. Since its expression is sensitive to non‐canonical Wnt signals and is reduced in colorectal tumours, downregulating RhoU may thus have an instrumental role in tumour progression. Abstract : Research article : RhoU is expressed in the differentiated epithelium of the intestine and is frequently downregulated in colorectal cancer (CRC). RhoU conditional invalidation in the gut increases epithelial cell density. This overcrowding effect, also observed in CRC cells depleted for RhoU, is a consequence of apoptosis inhibition. RhoU depletion is associated with increased cell contractility and RhoA activity. Taken together, these data suggest that RhoU downregulation is instrumental in cancer progression.